Proceso de atención nutricional en paciente masculino de 8 años de edad con anemia ferropénica y gastritis. - Gómez Medina, Mercedes Leonela (2022)
Iron deficiency anemia is a disease caused by iron deficiency, complicating the formation of red blood cells, which are responsible for providing oxygen to the body's tissues. Iron deficiency is one of the most common causes of anemia. Iron deficiency anemia is mild and can go unnoticed, but as time goes by, its symptoms become more aggressive and the anemia worsens. Gastritis on the other hand is inflammation of the stomach, these two diseases are associated with peptidic ulcers. The priority of this clinical case is to improve the nutritional status of the pediatric patient with a 10-week evolution through dietary-therapeutic treatments, collecting anthropometric data, clinical history, biochemical data, among others; Data we use to determine treatment and choose the appropriate treatment. The results obtained after 1 month of treatment report a change in the nutritional status of the patient who arrived with a diagnosis of iron deficiency anemia and gastritis. This is the product of the diet-therapeutic treatment according to your nutritional needs.